1996
DOI: 10.1007/bf00033096
|View full text |Cite
|
Sign up to set email alerts
|

In vitro techniques for selecting wheat (Triticum aestivum L.) for Fusarium-resistance. II. Culture filtrate technique and inheritance of Fusarium-resistance in the somaclones

Abstract: Calli of resistant, intermediary and susceptible wheat (Triticum aestivum L .) varieties were selected using culture filtrates of Fusarium graminearum and F culmorum and the regenerants were evaluated for resistance up to R3 .Czapek-Dox broth medium was inoculated with mycelia of Fusarium isolates and incubated for 2-6 weeks . Filtrates were added to MS callus growing medium, then 5 weeks-old calli were transferred onto this medium (MST) for 4-5 weeks . MST containing 30% filtrate was found to be suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 30 publications
0
7
0
3
Order By: Relevance
“…Modern-day field maize cultivars are almost universally infected with symptomless endophytic colonizations by F. verticillioides (Foley, 1962;Kommedahl and Siggerirsson, 1975;Thomas and Buddenhagen, 1980;Leslie et al, 1990;Ahmed et al, 1996;Anaya and Roncero, 1996;Bai, 1996;Bakan et al, 2002), but disease symptoms are rarely exhibited unless stressed. Plant breeding and selection may have formed the basis for symptomless root infection in maize and possible other agricultural species and cultivars.…”
Section: Life Cyclementioning
confidence: 98%
“…Modern-day field maize cultivars are almost universally infected with symptomless endophytic colonizations by F. verticillioides (Foley, 1962;Kommedahl and Siggerirsson, 1975;Thomas and Buddenhagen, 1980;Leslie et al, 1990;Ahmed et al, 1996;Anaya and Roncero, 1996;Bai, 1996;Bakan et al, 2002), but disease symptoms are rarely exhibited unless stressed. Plant breeding and selection may have formed the basis for symptomless root infection in maize and possible other agricultural species and cultivars.…”
Section: Life Cyclementioning
confidence: 98%
“…Plant improvement through somaclonal variation and in vitro selection is some techniques of in vitro culture for obtaining plant genotype tolerance to the biotic or abiotic stress, such as drought, high salinity, Al stress, acid soil, and disease tolerance (Ahmed et al, 1996;Yusnita et al, 2005). In addition, the plants are expected to have some desired characters such as having bigger fruit size, more interesting flower texture, more delicious taste and higher production (Pedrieri, 2001;Ahloowalia and Maluszynski, 2001;Witjaksono, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In earlier, in vitro plant regeneration via micropropagation (Purkayastha et al, 2008;Karuppusamy and Kalimuthu, 2010;Jindal et al, 2015) and somatic embryogenesis (Martin, 2004) have been reported in A. paniculata. Now a day, in vitro selection and somaclonal variation techniques are utilized for attaining plant genotype tolerance to the abiotic stress like high salinity, drought, heavy metal stress, acid soil and disease tolerance over biotic stresses (Ahmed et al, 1996;Yusnita et al, 2005). In vitro selection is an effective method to alter the plant with desired character through applying a selective agent on media (Bulk, 1991).…”
Section: Introductionmentioning
confidence: 99%